Denaturasi Protein - Anang Lukmana (Balai Besar Kimia dan Kemasan, 1976)
Protein denaturation is a decomposition process which is followed by chemical physical and biologgical changes of protein properties. Changes in chemical properties cause decreasing of solubility. while changes in physical and biological properties will cause increasing of concentration and increasing of divestibility by proteolitic enzymes, respectively Protein denaturation can occur either through physical or chemical processes.